MDL Mean Function Selection in Semiparametric Kernel Regression Models - Jan G. De Gooijer; Ao Yuan (Tinbergen Institute, 2008)
We study the problem of selecting the optimal functional form among a set of non-nested nonlinear mean functions for a semiparametric kernel based regression model. To this end we consider Rissanen's minimum description length (MDL) principle. We prove the consistency of the proposed MDL criterion. Its performance is examined via simulated data sets of univariate and bivariate nonlinear regression models.
Keywords: C14; 330; Kernel density estimator; Maximum likelihood estimator; Minimum description length; Nonlinear regression; Semiparametric model; Regression; Maximum-Likelihood-Methode; Nichtlineares Verfahren; Nichtparametrisches Verfahren; Theorie